The Effect of Flash Card Games on Early Children's Reading Ability - Jamila Jamila; A. Zulkarnain Ali; Pascalian Hadi Pradana (SAINTIS Publishing, 2025)
The purpose of this study was to determine whether flashcard games influence the reading skills of young children. The problem of low reading skills in early childhood remains a serious challenge in Indonesia. Various studies and national data show that most children aged 5–6 years have not yet mastered early reading skills appropriate to their developmental stage. This condition is exacerbated by the lack of engaging learning media and the lack of innovative approaches in reading instruction. The use of conventional methods tends to make children bored and unmotivated to learn to read. Therefore, interactive, fun solutions are needed that are appropriate to the characteristics of early childhood. One potential solution is the use of game-based learning media such as flashcards. Flashcards are visual media that can increase children's interest in letters and words while also fostering the association process between images and written symbols. The use of flashcards can improve visual memory, accelerate letter recognition, and create a fun learning atmosphere. Several studies have shown that this method is effective in improving early childhood reading skills, particularly in aspects of letter recognition and early reading as a whole. This study aimed to determine the effect of flashcard games on early childhood reading skills. The method used was an experiment with a one-group pretest-posttest design. Subjects were given a pretest, then given treatment using flashcards, and then a posttest. Data collection was conducted through observation using indicators of language and reading development. Data analysis used a paired sample t-test to determine the significance of changes before and after treatment.